Newly developed index for genomic breeding value based selection of dairy cattle in Tanzania - CGIAR Research Program on Livestock (2020)
The Platform for Africa Dairy Genetics Gain (ADGG)July 2020New Index for dairy cattle in Tanzania and guidelines on its use